2014
DOI: 10.1002/hbm.22694
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functional and macrostructural brain changes in Parkinson's disease and multiple system atrophy

Abstract: Parkinson’s disease (PD) and the parkinsonian variant of multiple system atrophy (MSAp) are neurodegenerative disorders that can be difficult to differentiate clinically. This study provides the first characterization of the patterns of task-related functional magnetic resonance imaging (fMRI) changes across the whole brain in MSAp. We used fMRI during a precision grip force task and also performed voxel-based morphometry (VBM) on T1-weighted images in MSAp patients, PD patients, and healthy controls. All grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 87 publications
6
66
0
Order By: Relevance
“…The fMRI protocol consisted of a block-design that alternated force and rest blocks as follows: 30 s rest, 30 s force with performance feedback, 12.5 s rest, and 30 s force without performance feedback [Burciu et al, 2015; Neely et al, 2014; Planetta et al, 2014; Prodoehl et al, 2010; Spraker et al, 2010]. This sequence was repeated four times and there was an additional 30-s rest period following the final block of force without performance feedback.…”
Section: Methodsmentioning
confidence: 99%
“…The fMRI protocol consisted of a block-design that alternated force and rest blocks as follows: 30 s rest, 30 s force with performance feedback, 12.5 s rest, and 30 s force without performance feedback [Burciu et al, 2015; Neely et al, 2014; Planetta et al, 2014; Prodoehl et al, 2010; Spraker et al, 2010]. This sequence was repeated four times and there was an additional 30-s rest period following the final block of force without performance feedback.…”
Section: Methodsmentioning
confidence: 99%
“…Acquisition of fMRI is usually performed during specific tasks (e.g., motor tasks). Motor control studies using fMRI engage an extensive task-related network including the basal ganglia, cerebellum, and motor cortex in healthy subjects, and defective activation of these structures in PD, MSA and PSP (Planetta et al, 2015). A study assessing longitudinal fMRI changes over the course of 1-year in PD, MSA, and PSP using a hand-grip-force paradigm showed reduced fMRI signal and more widespread and more pronounced changes in basal ganglia, cerebellum, and motor cortex in patients with MSA and PSP compared to PD (Burciu et al, 2016).…”
Section: Brain and Cardiac Neuroimagingmentioning
confidence: 99%
“…1a) because previous studies have shown reliable blood oxygen level-dependent (BOLD) activity changes in individuals with neurological disorders that include Parkinson’s disease, essential tremor, multiple system atrophy, and progressive supranuclear palsy (Burciu et al 2015; Neely et al 2015; Planetta et al 2015a; Spraker et al 2010). Further, our pilot data confirmed that SCA6 patients were able to execute pinch grip force with similar behavioral performance as age-matched healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…In the no vision block, the green bar did not move, and the subject had to produce the force from memory. We did not have a specific hypothesis for the vision and no vision blocks, and we used this paradigm because it is well-validated in prior studies and the paradigm elicits a robust BOLD signal across the cortex, basal ganglia, thalamus, and cerebellum (Burciu et al 2015; Neely et al 2015; Planetta et al 2015a). Participants completed eight total blocks (four vision and four no-vision) during the fMRI session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation